2010
DOI: 10.1177/0022034510366846
|View full text |Cite
|
Sign up to set email alerts
|

Dental Pulp Cells for Induced Pluripotent Stem Cell Banking

Abstract: Defined sets of transcriptional factors can reprogram human somatic cells to induced pluripotent stem (iPS) cells. However, many types of human cells are not easily accessible to minimally invasive procedures. Here we evaluated dental pulp cells (DPCs) as an optimal source of iPS cells, since they are easily obtained from extracted teeth and can be expanded under simple culture conditions. From all 6 DPC lines tested with the conventional 3 or 4 reprogramming factors, iPS cells were effectively established fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
156
4
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(165 citation statements)
references
References 34 publications
(38 reference statements)
3
156
4
2
Order By: Relevance
“…Therefore, NCCs could represent a key cell source for tooth-tissue engineering. Induced pluripotent stem (iPS) cells are generated from a variety of somatic cells such as dermal fibroblasts (53,54), blood cells, (12) and dental pulp cells (42,55,59,62) by induction with several factors. iPS cells are able to differentiate into all three germ layers with large-scale expansion (12, 42, 53-55, 59, 62), bypassing the potential ethical problems of using embryonic stem (ES) cells.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, NCCs could represent a key cell source for tooth-tissue engineering. Induced pluripotent stem (iPS) cells are generated from a variety of somatic cells such as dermal fibroblasts (53,54), blood cells, (12) and dental pulp cells (42,55,59,62) by induction with several factors. iPS cells are able to differentiate into all three germ layers with large-scale expansion (12, 42, 53-55, 59, 62), bypassing the potential ethical problems of using embryonic stem (ES) cells.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, iPS cells offer the potential to derive patient-and lineage-specific cells for clinical applications and have emerged as a potential cell source for regenerative medicine and tissue engineering. Previous studies suggested that cell proliferation ability (42,59) or endogenous expression of reprogramming factors (10,55) in parent cells is positively related to the reprogramming efficiency. Human dental pulp cells as parent cells for iPS cells exhibit higher reprogramming efficiency than do human dermal fibroblasts (42,55) because they show rapid cell proliferation (42) and high expression of endogenous reprogramming factors, c-MYC and KLF4 (55), compared to human dermal fibroblasts.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The biological constraints, which become better characterized as research progresses, will necessarily restrict the number of protocols and strategies. Potential human cell sources have been reported (Gronthos et al, 2000;Miura et al, 2003), while banks for autologous cell sources are being developed (Arora et al, 2009;Tamaoki et al, 2010;Woods et al, 2009). The biological potentialities of the different cells types, which recently were identified from human sources, will have to be tested both in vitro and in vivo.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%